Association between Finger Tapping, Attention, Memory, and Cognitive Diagnosis in Elderly Patients. Issue 1 (August 2014) - Rabinowitz, Israel; Lavner, Yizhar
This study examined the association between spontaneous finger tapping and cognitive function, with a detailed analysis of the two main phases of finger tapping, the touch-phase and the off-phase. 170 elderly patients (83 men, 87 women; M age = 82.1yr., SD = 6.2) underwent cognitive assessment including the Mini-Mental State Examination, a forward digit span test, and 15sec. of finger tapping. Results indicated a significant increase in the length and variability of the finger-touch phase among participants with mild cognitive impairment or dementia compared to participants with no cognitive impairment, suggesting a relationship between finger tapping and attention, short-term memory, and cognitive diagnosis. Pattern classification analyses on the finger tapping parameters indicated a specificity of 0.91 and sensitivity of 0.52 for ruling out cognitive impairment.